Barriers and facilitators of effective self-management in asthma: systematic review and thematic synthesis of patient and healthcare professional views. (December 2017) - Miles, Clare; Arden-Close, Emily; Thomas, Mike; Bruton, Anne; Yardley, Lucy; Hankins, Matthew; Kirby, Sarah
Abstract Self-management is an established, effective approach to controlling asthma, recommended in guidelines. However, promotion, uptake and use among patients and health-care professionals remain low. Many barriers and facilitators to effective self-management have been reported, and views and beliefs of patients and health care professionals have been explored in qualitative studies. We conducted a systematic review and thematic synthesis of qualitative research into self-management in patients, carers and health care professionals regarding self-management of asthma, to identify perceived barriers and facilitators associated with reduced effectiveness of asthma self-management interventions. Electronic databases and guidelines were searched systematically for qualitative literature that explored factors relevant to facilitators and barriers to uptake, adherence, or outcomes of self-management in patients with asthma. Thematic synthesis of the 56 included studies identified 11 themes: (1) partnership between patient and health care professional; (2) issues around medication; (3) education about asthma and its management; (4) health beliefs; (5) self-management interventions; (6) co-morbidities (7) mood disorders and anxiety; (8) social support; (9) non-pharmacological methods; (10) access to healthcare; (11) professional factors. From this, perceived barriers and facilitators were identified at the level of individuals with asthma (and carers), and health-care professionals. Future work addressing the concerns and beliefs of adults, adolescents and children (and carers) with asthma, effective communication and partnership, tailored support and education (including for ethnic minorities and at risk groups), and telehealthcare may improve how self-management is recommended by professionals and used by patients. Ultimately, this may achieve better outcomes for people with asthma.